Beyond D'Arcy Thompson: Future challenges for quantitative biology. (June 2017) - Gregor, Thomas
Abstract: The centennial of "On Growth and Form" is a good opportunity to reflect on the progress of the quantitative study of living systems and where we would like to see it heading. The era of the physical sciences being a mere vehicle for tool building for biological investigations is over. The approaches taken nowadays are analogous to those that physical scientists have taken within their respective fields for centuries, only that now they ask them about biological phenomena and function. Here I give a brief reflection on where we are and where we should direct our focus next, both from the perspective of the research endeavor as a whole, but also with respect to teaching the next generation of scientists joining the field.